_
0
Af(X(t))dt
_
<
Page 17, line 5 the integrals
_
R
should be replaced by
_
U
for all U B
0
Page 18, the rst 5 lines should be replaced with:
dX(t) = (t)dt +
_
R
(t, z)
N(dt, dz)
= (t)dt +
_
R
(t, z){
N
Q
(dt, dz) (t, z)(dz)dt}
=
_
R
(t, z)
N
Q
(dt, dz),
Page 18, replace line 6 by
Z(t) := exp
_
j=1
t
_
0
_
R
_
ln(1
j
(s, z
j
))
N
j
(ds, dz
j
) + (ln(1
j
(s, z
j
)) +
j
(s, z
j
))
j
(dz
j
)ds
_
Page 19, replace line 3 by
(dz) =
1
(dz)
where
1
(dz)is the unit point mass at 1.
Page 19, replace z
1
by 1 in (1.4.17) and the two lines below.
Page 20, correct inequality (1.5.1) to
_
R
z(dz) >
,
and on the line below replace
r
by
,
Page 20, the two lines below equation (1.5.2) should be changed to:
By (1.5.1) we see that if A B
0
with
<
_
A
z(dz) := K < then
(z) =
r
K
X
A
(z) signz
Page 20, two lines above (1.5.3), replace (1, ) by B
0
.
1
Page 20 replace line 7 by
Z(t) = Z
(t) = exp
_
t
_
0
_
R
ln(1 (z))
N(ds, dz) +t
_
R
{ln(1 (z)) +(z)}(dz)
_
; 0 t T
Page 21, 5 lines below (1.5.8), replace rV
(t) by rV
(t)dt
Page 25, line 9 replace
ij
by
ij
.
Page 25, correct equation (1.6.3) to
_
R
z
i
(dz) > 
i1
1
+
i2
2
 for i = 1, 2.
Page 29, line 12,11: correct condition (viii) to
E
y
_
(Y ()) +
S
_
0
A(Y (t))dt
_
<
Page 31, rst line below (2.2.1): replace z > 1 a.s. by 1 < z 0 a.s. .
Page 34, line 5 should be corrected to
A(s, x) +f(s, x) e
s
(( )x + ( +a),
where = (R).
Page 34, lines 710 should be corrected to
A(s, x) +f(s, x) 0
1
+
+
Page 35, line 6, replace z > 1 a.s. by z > 1 a.s.
Page 36, Theorem 2.6.: The assumption
1
+
+
should be added
Page 36, Exercise 2.1: Assume that z 0 a.s. .
Page 36, Exercise 2.2: Assume that z 0 a.s. .
Page 37, Exercise 2.3: Change line 4 to
dX(t) = dB(t) +
_
R
(X(t), z)
N(dt, dz)
Page 37, last sentence of Exercise 2.3 should be changed to:
Assume that there exists > 0 such that
(x, z) = 0 for a.a. z if x < (2.3.1)
(x, z)(x ) 0 for a.a. z if x (2.3.2)
and
tgh(
_
2 )
1
2
.
Page 40, line 8,7 correct condition (iii) to
E
y
_
(Y ()) +
S
_
0
A(Y (t))dt
_
<
2
Page 59, rst line below (4.1.1): Replace z 1 a.s. by z 0 a.s. .
Page 62, line 1,2 correct condition (viii) to
E
y
_
(Y
(u)
()) +
S
_
0
A(Y
(u)
(t))dt
_
<
Page 74, line 2,3 correct condition (iii) to
E
y
_
(Y ()) +
S
_
0
A(Y (t))dt
_
<
Page 78, Exercise 5.1: Assume that z 0 for a.a. z .
Page 84, line 4,5 correct condition (ix) to
E
y
_
(Y ()) +
S
_
0
A(Y (t))dt
_
<
Page 86, equation (6.2.1): Assume that z 0 a.s. .
Page 90, equation (6.2.17): Assume that z 0 a.s. .
Page 94, Exercise 6.1: Change the state equation to
dX
(v)
(t) = dB(t) +
_
R
(X
(v)
(t), z)
N(dt, dz);
k
< t <
k+1
X
(v)
(
k+1
) =
X
(v)
(
k+1
) +
k+1
; k = 0, 1, 2, . . .
Page 94, Exercise 6.1: Replace the symmetry assumption on by the following
assumption: There exists > 0 such that
(x, z) = 0 for a.a. z if x < (6.3.1)
(x, z)(x ) 0 for a.a. z if x (6.3.2)
Page 94, Exercise 6.2: Assume that 1 z 0 a.s. .
Page 95, Exercise 6.3: Assume that z 0 a.s. .
Page 107, last line: replace
j
R by
j
< 0.
Page 108, change the rst two sentences to:
This is a nite number of interventions version of Example 6.5, where we for simplicity have
put = 0. We assume that z 0 a.s. .
Page 108, correct (7.2.8) to:
1
(x) =
_
1
x
2
+
b
2
a
1
exp(r
1
x) ; x < x
1
b
2
+c ; x x
1
,
Page 109, line 3: Correct x = x
1
to x = x
1
Page 109, formula (7.2.9): replace cosh by exp
Page 109, formula (7.2.10): replace sinh by exp
Page 109, correct (7.2.11) and (7.2.12) to:
x
1
=
1
r
1
_
1 +
_
1 +cr
2
1
_
(7.2.11)
a
1
=
2x
1
r
1
exp(r
1
x
1
) (7.2.12)
Page 109, delete (7.2.13) and the following sentence.
3
Page 110, formula (7.2.15) and (7.2.18), replace cosh by exp and x by x.
Page 110, correct (7.2.16) and (7.2.17) to
x
2
=
1
r
1
_
1 +
_
1 + (c a
1
)r
2
1
_
(7.2.16)
a
2
=
2x
2
r
1
exp(r
1
x
2
). (7.2.17)
and delete the rst sentence right below.
Page 110, correct (7.2.19) and (7.2.20) to
x
n
=
1
r
1
_
1 +
_
1 + (c a
n1
)r
2
1
_
(7.2.19)
a
n
=
2x
n
r
1
exp(r
1
x
n
). (7.2.20)
Page 111, formula (7.2.21): replace cosh by exp and x by x.
Page 111, correct (7.2.22) and (7.2.23) to
x
=
1
r
1
_
1 +
_
1 + (c a)r
2
1
_
(7.2.22)
a =
2x
r
1
exp(r
1
x
). (7.2.23)
Page 115, Line 10,11 correct condition (ix) to
E
y
_
(Y ()) +
S
_
0
A(Y (t))dt
_
<
Page 153 line 1, 2, 5, 6 in conditions (i), (ii), (iii), (iv), replace
1
(z) by z
1
(z),
2
(z)
by z
2
(z),
1
by
1
,
2
by
2
.
Page 153, line 7, replace R by B
0
.
Page 153, line 8, correct the inequality to

i1
1
+
i2
2
 <
_
Ai
z
i
(dz) = K
i
<
Page 153, line 10, correct the equality to
i
(z) = signz
i1
1
+
i2
2
K
i
X
Ai
(z) ; i = 1, 2
Page 153, line 12, correct the equality to
Z(t) = exp
_
2
i=1
_
t
_
0
_
R
ln(1
i
(z
i
))
N
i
(ds, dz
i
)+
_
t
0
_
R
{ln(1
i
(z))+
i
(z)}
i
(dz)
__
; 0 t T
Page 155: lines 34 from (vi): correct these lines to
A(s, x) e
s
((x a) +c) .
So (vi) holds if e
1a+1
Page 155: Replace (10.2.6) by
z 0 a.s. (10.2.6)
4
Page 160, line 3: change this line to
F() := +
1
2
2
= 0.
Page 162, line 6: replace B(t) = x
by X(t) = x
.
Page 173, lines 34 after (i): correct these lines to:
e
s
(A(s, x) +f(s, x))
1 +
x +
1 +
C
3
Page 175, line 2 can be simplied to
A
0
(x) +f(x) := (x) +
1
2
(x) +x
2
= 0.
Page 176, line 1 should be corrected to
(x) = C cosh(x) +
1
x
2
+
1
2
; =
_
2
Page 176, lines 39 can be deleted
Page 176, line 11: Correct this to
0
(x) :=
1
x
2
+
1
2
a cosh(x)
Page 179, rst line of Conclusion: Assume that x .
Page 182, third line after (vi) should be corrected to
A
0
(x) = (1 +)
1
[( )x + ( +)c].
and the corresponding inequality on line 4 above Exercise 6.3 hence becomes
1
+
+
.
Hence (vi) holds if is small enough.
Page 184, line 13 should be corrected to
A
0
(x) = (1 )x +(c M) +(1 ) +c.
and this gives the conclusion that for (vi) to hold we need to assume that
+
c
1
.
Page 188, line 3 below (vi): correct this to
If x > x
1
then L
0
1
(x) 0 if x
c(+)
1
0 for all x x
1
if is small enough.
We want to thank Andreas Kyprianou for valuable comments.
5